Health treaty dilution: a case study of Japan's influence on the language of the WHO Framework Convention on Tobacco Control - Assunta, Mary (BMJ Group, 2006)
BACKGROUND: The Japanese government is an important shareholder in the Japanese tobacco industry. Negotiations to develop the WHO's historic Framework Convention on Tobacco Control (FCTC) were based on consensus, resulting in countries needing to agree to the lowest acceptable common denominator in clause development. OBJECTIVE: To illustrate Japan's role in negotiating key optional language in the FCTC text. METHODS: Summary reports, text proposals, conference papers, and speeches related to the six FCTC negotiation sessions were reviewed for repeated words, concepts and emerging themes. Key stakeholders were interviewed. Key words such as “sovereignty”, “appropriate”, “latitude”, “individual”, “flexibility”, and “may” representing optional language were examined. RESULTS: The Japanese government's proposals for “appropriate” and optional measures are reflected in the final FCTC text that accommodates flexibility on interpretation and implementation on key tobacco controls. While Japan was not alone in proposing optional language, consensus accommodated their proposals. CONCLUSION: Japan's success in arguing for extensive optional language seriously weakened the FCTC. Accordingly, international tobacco control can be expected to be less successful in reducing the burden of disease caused by tobacco use.